Re/coding Global Citizenship: How Information and Communication Technologies have Altered Humanity… and Created New Questions for Global Citizenship Education - Gabriel Swarts (Research in Social Sciences and Technology- OpenED Network, 2020)
In the broadest sense, the concept of global citizenship education (GCE) includes many facets of a rapidly changing world and concepts in education. The information and communication technology (ICT) advances of the last few decades have created opportunities for educational connection and interaction through digital spaces at all levels, local and global. In linking technology with global citizenship, neither GCE nor ICTs can be assumed to be mutually progressive and/or mutually beneficial. In recent years, governments have moved to centralize ICT technologies exacting more control over their use for surveillance, including the weaponization of ICTs for strategic gains. This complicates the work of GCE scholars and practitioners in unforeseen ways as centralized control limits decentralized interactions. ICT concepts and philosophical stances are explored and defined to address how GCE scholars and practitioners can reimagine and reframe the tenets of the field within this informational world. Key topics discussed include complications of GCE in the infosphere, digital citizenship & GCE, and teaching GCE in the age of “inforgs” & digital identities.